On some problems of using the Human Development Index in economic history - Nicola Amendola; Giacomo Gabbuti; Giovanni Vecchi (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2021)
We argue against the use of composite indices, such as the Human Development Index (HDI), in economic history. We show that the HDI can be interpreted as a formal representation of the analyst's ethical system. We support our claim by introducing a new class of paternalistic social welfare functions (Graaff 1957, Mas-Colell, 1995) which encompasses all the HDI formulas put forth by the literature. The theoretical framework is illustrated by an empirical investigation of the long-run evolution of Italians' living standards and civic liberties. We conclude that any history based on composite indices is one where both data and history play a minor role, if any.
Keywords: N01; N3; O15; 330; Human development index; economic wellbeing; composite indices; living standards; CES; social welfare functions; Italy